Nimotuzumab for Patients With Inoperable Cancer of the Head and Neck - Crombet Ramos, Tania; Mestre Fernández, Braulio; Mazorra Herrera, Zaima; Iznaga Escobar, Normando E. (Frontiers in Oncology, 2020)
EGFR activation induces cell proliferation, neoformation of blood vessels, survival and metastasis of the cancer cells. Nimotuzumab is an engineered, intermediate affinity anti-EGFR antibody, that apart from other drugs in its class, is very safe and does not cause hypomagnesemia or grade 3-4 cutaneous rash. The antibody inhibits cell proliferation and angiogenesis, activates natural killer cells, stimulates dendritic cell maturation and induces cytotoxic T cells. Nimotuzumab restores MHC-I expression on tumor cells, hindering one of the EGFR immune-escape ways. The antibody has been extensively studied in 7 clinical trials, concurrently with irradiation or irradiation plus chemotherapy in subjects with inoperable head and neck tumors. Nimotuzumab was safe and efficacious in unfit patients receiving irradiation alone and in subjects treated with cisplatin and radiotherapy. In patients with locally advanced squamous cell carcinomas of the head and neck, nimotuzumab in combination with low dose cisplatin and radiotherapy was superior to cisplatin and radiotherapy in progression free survival, disease free survival and locoregional tumor control.